Overview of the level of work stress of nurses in the central surgical installation room of Jampangkulon Regional Hospital in 2024 - Anggriawan, Yoga; Hamzah, Amir; Alamsah, Mustopa Saepul (Science Midwifery, 2025)
Job stress occurs when job demands exceed the capacity, resources, and abilities of nurses. Based on the results of previous interviews with several nurses at the Central Surgical Installation of Jampangkulon Hospital, they revealed that their biggest problems were the increasing number of patients, demands from other professions in one team that were so high on their performance, emergency situations also often required nurses to work quickly and accurately without making mistakes. These conditions are considered to be the cause of stress in nurses at the central surgical installation. This results in feelings of anxiety, fatigue, anger, frustration and internal conflict at the Central Surgical Installation of Jampangkulon Hospital. The researcher will use a quantitative descriptive research type with a Cross-sectional approach. The research sample was all nurses at the Central Surgical Installation of Jampangkulon Hospital, totaling 28 people. Data collection was carried out by filling out a questionnaire (NIOSH Generic Job Stress Questionnaire). The results of this study revealed that among nurses, job stress was evenly distributed 50% mild stress and 50% severe stress. Factors that influence stress include the dominance of male respondents 60.7%, married status 92.9%, and DIII education level 64.2%. In addition, 82.1% of nurses are involved in low activities outside of work, and 57.2% of nurses have high social support. Therefore, researchers recommend that hospitals evaluate nurses' job descriptions and conduct effective communication before working. Effective communication is carried out to convey the roles and responsibilities of nurses clearly and workers can convey obstacles felt while carrying out their duties as nurses.